Standardization of fertigation scheduling in broccoli (Brassica oleracea var italica) - DEBBARMA, SAJAL; BHATT, LALIT; SINGH, P K; GAUTAM, POONAM; RAGHAV, MANOJ; LAVLESH, LAVLESH; SINGH, A K (The Indian Journal of Agricultural Sciences, 2021)
Efficient use of water and fertilizer is extremely critical to sustain the agricultural production, in the context of declining per capita land and water availability, pollution and increasing cost of fertilizers. A field experiment was conducted at Vegetable Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, India during the rabi 2016-17 and 2017-18 to study the effect of fertigation with levels and scheduling on growth, yield and economics of broccoli (Brassica oleracea var italica). The experiment was laid out in two factorial RBD with one additional treatment consisting of five fertigation levels and three fertigation scheduling along with one control (soil application of RDF with flooding) replicated thrice. The outcome of study revealed that fertigation of broccoli with water soluble fertilizer gave significantly higher plant growth, net return and benefit cost ratio as compared to the soil application of RDF with flooding (control). Fertigation treatments registered a significantly higher yield of 13.74 t/ha and it was higher by 15.96% over the conventional method of fertilization (11.85 t/ha).